Kikuchi-Fujimoto disease in the regional lymph nodes in a patient with concurrent malignant phyllodes tumour - Ciara Murray; Rosemarie Tremblay-LeMay; Jan Delabie; Andrea Covelli; Susan J. Done (Elsevier, 2024)
Kikuchi-Fujimoto disease (KFD, histiocytic necrotizing lymphadenitis) is a rare, benign disease in which the presenting clinical and radiological features often result in misclassification as a malignant process. We present the first report of concurrent KFD in the draining lymph nodes of a malignant phyllodes tumour, adding to the growing number of reports of KFD occurring in the context of malignancy, further compounding the existing diagnostic difficulties. An increased awareness of this condition with consideration for inclusion in the differential diagnosis of lymphadenopathy is required for improved diagnosis of this under-recognized entity.